THE MEDIATING ROLE OF JOB SATISFACTION IN THE EFFECT OF WORK-LIFE BALANCE ON ORGANIZATIONAL COMMITMENT(A Study on the Staff of the Tourism Management Agency of the Outer Area of Uluwatu Temple) - Putu Bayu Dea Laksana; I Gusti Ayu Manuati Dewi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the mediating role of job satisfaction in the relationship between work-life balance and organizational commitment among staff of the Tourism Management Agency of the Outer Area of Uluwatu Temple. A non-probability purposive sampling technique was applied, involving 91 respondents. Data collection was conducted through surveys and interviews. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that work-life balance has a positive and significant effect on organizational commitment, work-life balance has a positive and significant effect on job satisfaction, job satisfaction positively and significantly affects organizational commitment, and job satisfaction is proven to partially and complementarily mediate the effect of work-life balance on organizational commitment.